Efeitos da variação do teor de umidade da madeira no processo de lixamento - Lima, Larissa Ribas de [UNESP] (2013)
The process of sanding wood is little known and industries use it in a practical way without having studied their best conditions before. There are few studies involving this type of machining. On this basis, this paper studied the effects of varying moisture content of the wood surface quality after the sanding process. It was used a sanding machine with flat horizontal cut parallel to the fibers, using: 02 different species (Pinus elliottii and Corymbia citriodora); 01 sanding abrasive (aluminum oxide) and 03 different particle size abrasives ( P80 , P100 and P120 ) . Initially, the pieces were acclimatized ( 2 ± 7% , 12% and 17% ± 2 ± 2 ) and subsequently passed by the sanding process, and therefore, the surface roughness was analyzed. For each condition, were performed 06 repetitions totaling 54 trials for each species. We analyzed the effects of wood moisture by capturing the power sanding, rougheness, acoustic emission and maximum temperature during the sanding process. The variation of moisture content produced changes in the surface quality of the finished parts, and these changes were more marked in Pinus than Corymbia. During the sanding process of the specimens with 7 % and 12 % humidity, there was a lower noise emission, power consumption and heating surface. When checking the roughness of these parts after this process, it was observed that the surface quality of them were superior in the parts sanded containing 17 % moisture